Near-Direct Bandgap WSe2/ReS2 Type-II pn Heterojunction for Enhanced Ultrafast Photodetection and High-Performance Photovoltaics - Varghese, Abin; Saha, Dipankar; Thakar, Kartikey; Jindal, Vishwas; Ghosh, Sayantan; Medhekar, Nikhil V; Ghosh, Sandip; Lodha, Saurabh (Nano letters, 2020)
Pn heterojunctions comprising layered van der Waals (vdW) semiconductors have been used to demonstrate current-rectifiers, photodetectors, and photovoltaic devices. However, a direct or near-direct heterointerface bandgap for enhanced photogeneration in high light-absorbing few-layer vdW materials remains unexplored. In this work, for the first time, density functional theory calculations show that the heterointerface of few-layer group-6 transition metal dichalcogenide (TMD) WSe2 with group-7 ReS2 results in a sizable (0.7 eV) near-direct type-II bandgap. The interlayer IR bandgap is confirmed through IR photodetection, and microphotoluminescence measurements demonstrate type-II alignment. Few-layer flakes exhibit ultrafast response time (5 μs), high responsivity (3 A/W), and large photocurrent-generation and responsivity-enhancement at the hetero-overlap region (10–100×). Large open-circuit voltage of 0.64 V and short-circuit current of 2.6 μA enable high output electrical power. Finally, long-term air-stability and facile single contact metal fabrication process make the multifunctional few-layer WSe2/ReS2 heterostructure diode technologically promising for next-generation optoelectronics.